Developing a framework for professional practice in applied performance analysis - Martin, D.; Donoghue, P. G. O.; Bradley, J.; McGrath, D. (International Journal of Performance Analysis in Sport, 2021)
Applied performance analysts are increasingly seen as sports science professionals; however, there is no accepted framework for professional practice. The purpose of this study is to develop and validate a framework for professional practice in applied performance analysis (PA) which identifies the components of practice and the expertise underpinning it.